EXTRACTION AND ANALYSES OF PHYTOCHEMICAL COMPOUNDS FROM CITRUS HYSTRIX PEELS FOR MOLLUSCICIDAL ACTIVITIES - Taesotikul, Theerada; Kitcharoen, Nudchanart; Chinpaisal, Chatchai; Phuagphong, Patamawan; Nawanopparatsakul, Srisombat (Thai Bulletin of Pharmaceutical Sciences, 2022)
The objective of this work was to screen, identify, and quantify the phytocompounds contained within Citrus hystrix peel extracts, in different extraction solvents, for molluscicidal activities. The peel of C. hystrix was extracted through the process of maceration with methanol. The phytochemical compounds found within the crude methanolic extract were further isolated through fractional partition with various solvents including hexane, dichloromethane, and butanol. Using thin-layer chromatography, phytochemical screenings for triterpenes, steroids, phenolic compounds, and alkaloids were carried out for each extract/fraction. The stability of the extracts/fractions were studied under static storage and accelerated conditions. The findings revealed that methanol was a suitable solvent for primary extraction, due to the high number and yield of compounds found, including non-polar, medium polar and high polar substances. After fractional extraction, non-polar compounds retained within hexane layer whereas both polar and medium polar substances were detected in methanol extract, dichloromethane and butanol fractions. The extracts were stable in normal storage conditions. Thus, this investigation could be of use for those conducting further research into the pharmacological activities of compounds contained within C. hystrix peel.